The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1007/bf00999489
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the developmental plasticity in the human cerebral cortex: The role of the transient subplate zone

Abstract: We correlated neuroanatomical developmental parameters with sequential ultrasonography scans to reveal the structural basis of functional recovery after early focal hypoxic lesions of the human frontal lobe in premature infants. We studied the transient fetal subplate zone in the premotor and prefrontal cortex in premature, newborn, infant, and young adult brains by acetylcholinesterase (AChE) histochemical, Golgi, and immunocytochemical methods. The structural in vivo rearrangements of the cerebral wall after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 16 publications
3
40
0
2
Order By: Relevance
“…Similar disruption of axonal outgrowth of the pyramidal neurons has been observed in Golgi-stained neuropathological samples from infants who have survived the preterm period (30). A significant complication of WM damage is the localized disruption of axon fibers resulting in the loss of inputs and outputs to and from the overlying areas of gray mater (31). The clinical correlate of even a minimal amount of such WM injury could be cerebral palsy, dyslexia, epilepsy, audiovisual deficits, and learning deficits.…”
Section: Discussionmentioning
confidence: 73%
“…Similar disruption of axonal outgrowth of the pyramidal neurons has been observed in Golgi-stained neuropathological samples from infants who have survived the preterm period (30). A significant complication of WM damage is the localized disruption of axon fibers resulting in the loss of inputs and outputs to and from the overlying areas of gray mater (31). The clinical correlate of even a minimal amount of such WM injury could be cerebral palsy, dyslexia, epilepsy, audiovisual deficits, and learning deficits.…”
Section: Discussionmentioning
confidence: 73%
“…5 In animal experiments, it has been shown that this transient fetal circuitry of the subplate zone is functional, 23,24 characterized by endogeneous spontaneous activity and involved in several activity-dependent events such as the formation of ocular dominance columns in the fetal visual cortex. 25,26 As the transient subplate zone is best developed in humans and at the peak of its development is four times thicker than the cortical plate 5 and contains well-differentiated neurons, 4,10,27 it probably has a substantial role in development of cortical circuitry and generation of cortical activity in brains of preterm infants. In addition, experimental data suggest that thalamocortical activity can modulate the early spontaneous activity of transient subplate circuitry.…”
Section: Comparison Of Mri and Histological Findingsmentioning
confidence: 99%
“…Studies on the subplate neurons of the developing human cerebral cortex [63,64,71] have also provided information on the possible relationship between the subplate neurons and different kinds of periventricular lesions. The thickness of the subplate in the frontal lobe reaches a peak at around 22-34 weeks of gestation.…”
Section: The Subplate As a Waiting Compartmentmentioning
confidence: 99%
“…After a variable time period, these fibers enter the cortical plate and the subplate disappears, leaving cells scattered throughout the subcortical white matter [64,71], or the subplate neurons just die. The subplate neurons, which are present throughout the neocortex, reach a high degree of functional and morphological maturity early in life, making them uniquely susceptible to the effects of trophic factor deprivation or excitotoxicity.…”
Section: The Subplate As a Waiting Compartmentmentioning
confidence: 99%